RANCANG BANGUN SISTEM INFORMASI SPASIAL PERSEBARAN PETERNAKAN BERBASIS WEB (STUDI KASUS: KOTA DEPOK) - Achmad Hendiyanto; Zainul Arham; Eva Khudzaeva (UIN Syarif Hidayatullah Jakarta, 2017)
Animal Husbandry in Depok City is generally found in every small village in Depok. Good coverage of small, medium and large farms. Many obstacles faced by the farmers in Depok region. And lack of information about livestock diseases. Another obstacle arises when one of the breeders needs supplies or livestock germs for his farm. Department of Agriculture and Fisheries (DISTANKAN) is a legal entity engaged in the area of Depok city in supervising and controlling the pace of development of farms, so that it can record and monitor the development of livestock in the city of Depok, it is necessary an information system that can integrate nonspatial data and spatial data distribution of existing livestock locations in Depok City capable of processing administrative data so that the office can inform the general public about livestock. Spatial analysis function in Geographic Information System (GIS) can be applied to Depok's DISTANCE system. By providing coordinate point on a data with a certain scale to represent a criterion. Therefore, researchers conduct research and make spatial information system based on web distribution of farms to record and provide spatial information location of farms scattered. The development of the system used is a model RAD (Rapid Application Development) with Unified Modeling Language (UML) design tool. Spatial tools used areArcView 3.3 and Mapguide. The stages of RAD system development starts from the requirement planning phase, the workshop design phase and the immunization phase (implementation) until the system testing. The results of this study is a system that can provide information distribution of livestock data for the general public and related institutions, especially spatial based in WebGis view.